2015
DOI: 10.1038/nbt.3371
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization of the physicochemical properties of polymer-linked TLR agonists that enhance vaccine immunogenicity

Abstract: The efficacy of vaccine adjuvants such as Toll-like receptor agonists (TLRa) can be improved through formulation and delivery approaches. Here, we attached small molecule TLR-7/8a to polymer scaffolds (polymer-TLR-7/8a) and evaluated how varying physicochemical properties of the TLR-7/8a and polymer carrier influenced the location, magnitude and duration of innate immune activation in vivo. Particle formation by polymer-TLR-7/8a was critical for restricting adjuvant distribution and prolonging activity in drai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
410
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(446 citation statements)
references
References 58 publications
11
410
0
9
Order By: Relevance
“…Chemical conjugation of adjuvant compounds to protein antigens ensures delivery to the same endocytic compartment, and this approach has been shown to enhance both humoral and cellular immunity in preclinical mouse and NHP models (65)(66)(67). Notably, these studies revealed that aggregation of antigen-danger signal conjugates to form particulates was critical to their in vivo efficacy, results which motivated recent studies that demonstrated how polymer-conjugated TLR agonists show both enhanced efficacy and safety when engineered to aggregate into a particulate form (68). The incorporation of antigen or danger signals into particulate vehicles can also be achieved by conjugation of these components to the surface of nanoparticles (69), entrapment within lipid vesicles or capsules (70), or encapsulation within polymer particles (47) or VLPs (60).…”
Section: Optimizing Antigen Display To B Cellsmentioning
confidence: 91%
“…Chemical conjugation of adjuvant compounds to protein antigens ensures delivery to the same endocytic compartment, and this approach has been shown to enhance both humoral and cellular immunity in preclinical mouse and NHP models (65)(66)(67). Notably, these studies revealed that aggregation of antigen-danger signal conjugates to form particulates was critical to their in vivo efficacy, results which motivated recent studies that demonstrated how polymer-conjugated TLR agonists show both enhanced efficacy and safety when engineered to aggregate into a particulate form (68). The incorporation of antigen or danger signals into particulate vehicles can also be achieved by conjugation of these components to the surface of nanoparticles (69), entrapment within lipid vesicles or capsules (70), or encapsulation within polymer particles (47) or VLPs (60).…”
Section: Optimizing Antigen Display To B Cellsmentioning
confidence: 91%
“…1E). This effect may be explained by the fact that PamadiFectin contains a lipidic moiety, leading to the formation of 50-nm particles, which in turn may limit dissemination and enhance uptake by APCs, thereby avoiding excessive inflammation as recently described for a TLR7 agonist (25). PamadiFectin enhances the avidity of Abs generated in vivo against HIV-1 p24 Endpoint titer ELISAs were performed in duplicate using nonreducing (PBS) and reducing (8 M urea) washes after sample addition to evaluate the avidity of Abs generated in vivo against HIV-1 p24.…”
Section: Pamadifectin Enhances In Vivo Immune Responses Against Hiv-1mentioning
confidence: 94%
“…Nevertheless, the procedures applied to entrap TLR agonists inside polymeric carriers are often highly complex and yield ill-defined systems that suffer from burst releases of the TLR agonist (19) following in vivo application. Covalent ligation of TLR agonists to polymeric nanoparticles might provide chemically better-defined alternatives to physical (co)encapsulation systems, as recently nicely highlighted by the Seder laboratory (20).…”
mentioning
confidence: 99%
“…Nevertheless, the procedures applied to entrap TLR agonists inside polymeric carriers are often highly complex and yield ill-defined systems that suffer from burst releases of the TLR agonist (19) following in vivo application. Covalent ligation of TLR agonists to polymeric nanoparticles might provide chemically better-defined alternatives to physical (co)encapsulation systems, as recently nicely highlighted by the Seder laboratory (20).Here, we report on the design of self-assembled, pH-degradable TLR7/8 agonist-ligated nanogels that efficiently restrict the innate immune-activating properties of the molecular adjuvant to the injection site and its DLN. Degradable polymer nanogels were prepared by self-assembly of amphiphilic block copolymers composed of a hydrophilic, PEG-like polymer block based on methoxy triethylene glycol methacrylate (mTEGMA) and a hydrophobic polymer block based on pentafluorophenyl methacrylate (PFPMA) (21).…”
mentioning
confidence: 99%